Profile of Adaptive Physical Education Facilities and Infrastructure in Private and Public Schools: A Case in the City of Bandung (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
Facilities and infrastructure are essential to the learning process, especially in adaptive physical education learning for children with special needs. Special Schools (SS) need adequate facilities and infrastructure so that the learning process can be effective. The purpose of this study is to find out how to describe the level of availability of adaptive physical education learning facilities and infrastructure in SS throughout the city of Bandung. The research method uses a quantitative descriptive. The sample of this research is six public SS in Bandung city with a purposive sampling technique. The instrument used is an observation sheet based on the Regulation of the Minister of National Education Number 24 of 2007 concerning Standard Facilities and Infrastructure for Elementary, Junior, and High Schools in Indonesia. Data analysis uses quantitative description as outlined in the form of a percentage. The results showed that adaptive physical education learning infrastructure in special schools throughout Bandung in 2021-2022 was in the 'fair' category with a percentage of 44%, and infrastructure in the 'very good' category with a rate (of 86%). Details related to facilities and infrastructure are also explained.